Nano iron–copper alloys for tumor ablation: efficiently amplified oxidative stress through acid response. (14th August 2020) - Lv, Rongmu; Du, Keke; Liu, Qianqian; Meng, Xiangyu; Chen, Lizhu; Wang, Zhifei
Abstract : A zero-valent alloy material for the efficient treatment of cancer under the response of an acid. Abstract : Efficiently, enhancing intracellular oxidative stress via increasing intracellular hydroxyl radicals (˙OH), which is based on the Fenton reaction and lowering glutathione (GSH) is a promising approach for cancer treatment. Herein, we synthesized a new alloy nanomaterial, Fe5 Cu3 O@BSA (FCB) with good dispersity aimed at introducing copper ions to improve the Fenton reaction efficiency and reduce GSH. Under the weak acid microenvironment at the tumor, FCB can release Fe 2+ and Cu 2+ and the released free electrons are expected to combine with oxygen to further generate H2 O2, leading to an excessive production of H2 O2 in the cells. Meanwhile, the released Fe 2+ and Cu 2+ can not only perform a higher reaction efficiency on producing ˙OH but also consume GSH, which dramatically increases the intracellular oxidative stress in both directions. In vitro experiments showed that the incubation of human breast cancer cells (MCF-7 cells) with 100 μg mL −1 FCB nanoparticles resulted in a 65.9% mortality rate after 24 h. The in vivo experiments showed that FCB could effectively inhibit tumor growth. In this study, a therapeutic strategy based on metal biomaterials with good biocompatibility was established to effectively enhance oxidative stress and has great potential in tumor treatment.